High yielding variety, FOFIFA 189, released for irrigated lowland systems inn Madagascar - CGIAR Research Program on Rice (2021)
Old varieties dominate in irrigated lowland in Madagascar and in 2019, FOFIFA 187, was released together with three other varieties for Sri-rigated systems.